2019
DOI: 10.1002/ceat.201900357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurities and Oxidation on Hydroconversion of Waste Cooking Oil into Bio‐jet Fuel

Abstract: The influences of impurities and oxidation evolution of waste cooking oil on the preparation of bio-jet fuel via hydroconversion were studied. The hydrogenation active sites and acid sites were covered by heavy metals, sulfides, and basic nitrogen compounds, resulting in the increase of selectivity for bio-jet fuel by decreasing the selectivity of diesel, aromatics, and iso-alkanes. The effects of impurities, oxidation on the reaction pathway, and product distribution became more distinct with higher catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Regarding oligomerization of free fatty acids, if the unsaturated double bonds are not saturated, they may undergo oligomerization through Diels–Alder condensation to yield cyclic fatty acid units, comprising even C 30 –C 70 hydrocarbons . Hence, the relatively high content of the 365 °C + fraction can be explained by the occurrence of thermal transformations and oligomerization pathways competing with the desired HDO and isomerization routes . This oligomerization and Diels–Alder reactions inhibit catalyst activity due to coke formation and suggest that the efficiency of the hydrogenation of the double bonds is lower than expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding oligomerization of free fatty acids, if the unsaturated double bonds are not saturated, they may undergo oligomerization through Diels–Alder condensation to yield cyclic fatty acid units, comprising even C 30 –C 70 hydrocarbons . Hence, the relatively high content of the 365 °C + fraction can be explained by the occurrence of thermal transformations and oligomerization pathways competing with the desired HDO and isomerization routes . This oligomerization and Diels–Alder reactions inhibit catalyst activity due to coke formation and suggest that the efficiency of the hydrogenation of the double bonds is lower than expected.…”
Section: Resultsmentioning
confidence: 99%
“…52 Hence, the relatively high content of the 365 °C + fraction can be explained by the occurrence of thermal transformations and oligomerization pathways competing with the desired HDO and isomerization routes. 53 This oligomerization and Diels−Alder reactions inhibit catalyst activity due to coke formation and suggest that the efficiency of the hydrogenation of the double bonds is lower than expected. As a matter of fact, it has been described elsewhere that a low hydrodeoxygenation activity for sulfide NiMo/Al 2 O 3 catalysts leads to long-chained byproducts (up to 29%).…”
Section: Evaluation Of the Conversion Of Triglycerides To N-alkanesmentioning
confidence: 97%
“…Therefore, existing studies deeply explored to analyze the advanced hydro-processing methods, ensuring the feasibility and sustainability of bio-jet fuel hydroprocessing [48]. Correspondingly, it has been found that the type of acid-base catalyst used for bio-jet fuel hydrotreating is also a major factor in improving bio-jet fuel output [53]. Wei et al [43] reported that the structure and acid distribution of zeolite catalysts affecting the isomerization activity and selectivity of jet fuel hydrocarbons, and Bezergianni and Dimitriadis [39] studied non-sulfide-loaded zeolite catalysts for bio-jet fuels, which had a homogeneous pore structure, high concentration of active acid sites, and reusability, which were decisive factors for the action of non-sulfide-loaded zeolite catalysts.…”
Section: Bio-jet Fuelmentioning
confidence: 99%
“…209,210 Some of these compounds can inhibit the subsequent transformation of the waste cooking oil in the oleo-chemical industry. 211 The impurities can decrease the catalyst activity, inhibit the catalyst durability, induce saponification, and increase the separation cost. 212−214 Hence, the waste cooking oil needs to be pretreated and upgraded.…”
Section: Mo Keggin-type Heteropolyanions [Xm 12mentioning
confidence: 99%
“…The valorization of waste lipids will play a significant role in the production of higher value-added chemicals in the future. However, the impurities are viewed as limiting factors for the valorization of waste cooking oil, e.g., moisture, acidity, toxic compounds, and N-, P- and S-containing compounds. , Some of these compounds can inhibit the subsequent transformation of the waste cooking oil in the oleo-chemical industry . The impurities can decrease the catalyst activity, inhibit the catalyst durability, induce saponification, and increase the separation cost. Hence, the waste cooking oil needs to be pretreated and upgraded.…”
Section: Introductionmentioning
confidence: 99%